PENGGUNAAN GOOGLE FORM DALAM MENINGKATKAN EFEKTIVITAS EVALUASI PEMBELAJARAN DARING SISWA PADA MASA COVID19 DI SD IT BAITUL MUSLIM WAY JEPARA - Siti Ngafifah (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2020)
This article aims to determine the advantages and disadvantages of using Google Forms in evaluating student online learning during the Covid19 pandemic at SD IT Baitul Muslim Way Jepara, East Lampung. This study uses qualitative methods and data collection techniques using observation, interviews, and documentation. The learning process at SD IT Baitul Muslim was carried out using Whatsapp, Zoom, and cellphone media. However, when the learning evaluation arrives, both the daily, mid-semester, and end-semester evaluations of SD IT BM use Google Form because the application from Google is very easily accessible to anyone provided they have a gmail.com account. The results showed that the learning evaluation using Google Form implemented by SD IT Baitul Muslim Way Jepara East Lampung was less effective. Due to feature limitations, design, and lack of editing history. In the realm of assessment, teachers are expected to not only refer to one type of Learning Evaluation but need to apply assessment (evaluation), namely continuity, objectivity, comprehensive, practical and cooperative which aims to optimize the ongoing learning. The positive contribution of this article is expected to provide information to education actors to improve skills and integrity in various learning activities in general, as well as in distance learning (online) specifically to facilitate the learning evaluation process during the current Covid19 pandemic.